Photo-Thermal Conversion of Selective Coatings with Iron and Chromium Powder Additives - Amer, Mohammed Al-Ameen; A. Al-Tabbakh, Ahmed (Al-Nahrain Journal of Science, 2025)
This research explores the improvement of solar-to-thermal conversion efficiency in aluminum substrates coated with heat-resistant black paint enhanced by iron (Fe) and chromium (Cr) powders. Aluminum sheets were thoroughly cleaned and coated with a commercial black paint, followed by the application of Fe and Cr powders (both individually and combined) using an air-spraying method to ensure even distribution. The coatings’ morphology and uniformity were examined through optical and scanning electron microscopy, while their elemental makeup was assessed using energy-dispersive X-ray spectroscopy (EDS). The photo-thermal conversion capabilities were tested by exposing the coated substrates to solar radiation, with temperature monitored over time. Reflectance measurements were conducted using a pyrheliometer-like device, and spectral absorptance was analyzed via UV-Vis spectroscopy. The EDS results confirmed the effective incorporation of Fe and Cr into the coatings, with minor cross-contamination likely due to processing. Results show that adding Fe and Cr powders notably changes the surface morphology, increasing roughness and complexity, which enhances light trapping and absorption. Among the coatings, the Fe-modified sample showed the highest solar absorptance (96.23%) and the greatest temperature increase under irradiation, surpassing both the Cr-modified and combined Fe+Cr coatings. UV-Vis analysis revealed that Fe-containing coatings possessed the greatest integrated absorbance, especially within the visible spectrum (500–800 nm), aligning with their superior photo-thermal performance. These results highlight that integrating Fe powder into heat-resistant paint on aluminum substrates is an effective and practical approach to optimize solar-to-thermal energy conversion, offering promising applications in solar thermal collectors.